STUDIES ON SUPPLEMENTATION OF AZOTOBACTER AND ORGANIC MATTER ON GROWTH AND YIELD IN TOMATO (LYCOPERSICON ESCULENTUM) - M. SHAHEEDHA BEGAM; T. PANNEERSELVAM; M. B. VEDHA (The Bioscan, 2014)
The pot culture studies were found out to be the effect of Azotobacter along with different organic matter supplementation such as Azotobacter + PASIC Compost, Azotobacter + Farmyard Manure, Azotobacter+Pressmud Compost, Azotobacter alone on the enhancement of growth and yield in tomato (Lycopersicon esculentum). Artificial inoculation of Pythium aphanidermatum was done in the inoculated organic matter treatment 15 Days after sowing (DAS) to disease incidence of the pathogen. Among the five treatments, combination of Azotobacter + Pressmud Compost was found to be have maximum plant height (43.50 cm), increased dry weight of root (1.840 g/plant) and shoot(5.931 g/plant), increased chlorophyll content (2.79 mg g-1) and increased fruit yield (1001.9 gplant-1) followed by the treatments Azotobacter + PASIC Compost, AZT+ Farmyard Manure and Azotobacter alone with minimum plant height , decreased dry weight of root and shoot,decreased chlorophyll content and decreased fruit yield. In case of foliar spray of Pythium aphanidermatum, Azotobacter + Pressmud Compost were found to be least disease incidence (20.10 mm) followed by more disease incidence with the treatments Azotobacter + PASIC Compost (23.10 mm), Azotobacter + Farmyard Manure (25.02 mm) and Azotobacter alone (28.69 mm) as compared to control.